Venous thromboembolic complications in scoliosis surgery: a review of the literature - M.N. Lebedeva; A.A. Ivanova (Хирургия позвоночника)
Objective. To present modern scientific information on the problem of venous thromboembolic complications (VTECs) following scoliosis surgery in children and adolescents. Material and Methods. The search for scientific sources was carried out in the PubMed, GoogleScholar and eLibrary databases for the period of 2012–2024. The content of 57 articles covering the issues of frequency, etiology, risk factors for the development of venous thromboembolic complications and thromboprophylaxis in the pediatric cohort as a whole and in the cohort of children and adolescents operated on for scoliosis was analyzed. Results. The incidence of VTECs during surgical correction of scoliosis is insignificant and does not exceed 1.0 %. Etiology of VTEC is multifactorial, since there is both genetic predisposition and acquired risk factors. For children and adolescents, the most important factors are patient age, family or personal thrombotic history, surgical site, duration of surgical intervention more than 120 minutes, repeated and complicated surgeries, blood loss, anemia, infections, immobilization for more than 48 hours, long hospital stay, and the presence of chronic diseases or concomitant hemostatic disorder in the form of hypercoagulation. In adolescence, smoking, use of oral contraceptives and obesity are acquiring particular importance. It is recognized that the presence of four of these factors requires classifying the patient to a group with a high risk of developing venous thrombosis and embolic complications. Conclusion. Given the low incidence of VTECs in scoliosis surgery, potential risks of using anticoagulant drugs, as well as effective postoperative patient care through early activation and use of external compression devices, the drug prophylaxis in scoliosis surgery is not recommended. At the same time, the lack of regulatory documents on screening and prevention of VTECs for this category of patients is associated with difficulties in identifying those clinical cases where drug prophylaxis is absolutely indicated.